Pemanfaatan Card Game untuk Meningkatkan Minat Belajar Bahasa Inggris Siswa-Siswi Kelas 8 di SMP Negeri 2 Kaliwungu - Kisnanto, Yustina; Hapsari, Stepanie; Priskantya, Atalya; Anggraeny, Mutiara; Kusumastuti, Nathalie (LPPM UMRI, 2024)
Fulfilling the English learning needs of junior high school students by using qualified teaching aids is not easy for English teachers in rural Indonesia. To overcome this obstacle, SMP Negeri 2 Kaliwungu Boyolali collaborated with a team of four students and one lecturer of PBI UKSW in the program